Formulation Development and Characterization of pH Responsive Polymeric Nano-Pharmaceuticals for Targeted Delivery of Anti-Cancer Drug (Methotrexate) - Ullah, Farhad; Iqbal, Zafar; Khan, Amjad; Khan, Saeed Ahmad; Ahmad, Lateef; Alotaibi, Amal; Ullah, Riaz; Shafique, Muhammad (Frontiers in Pharmacology, 2022)
Oral administration of pH sensitive/stimuli responsive nanoparticles are gaining importance because of the limited side effects, minimum dose and controlled drug release. The objective of this study was to develop and evaluate pH sensitive polymeric nanoparticles for methotrexate with the aim to maximize the drug release at target site. In the presented study, pH sensitive polymeric nanoparticles of methotrexate were developed through modified solvent evaporation technique using polymer Eudragit S100. Different process parameters like drug to polymer ratio, speed of sonication, concentration of surfactant and time of sonication were optimized by evaluating their effects on particle size, PDI, zeta potential, entrapment/encapsulation efficiency. The developed formulations were evaluated for their size, polydispersity (PDI), zeta potential, encapsulation efficiency, XRD, scanning electron microscopy, in-vitro drug release and stability studies. Best results were obtained with poloxamer-407 and PVA and were selected as surfactants. Physicochemical characterization of the developed formulations showed that the particle size lies in the range 165.7 ± 1.85 to 330.4 ± 4.19, PDI 0.119 ± 0.02 to 0.235 ± 0.008, zeta potential -0.163 ± 0.11 to -5.64 ± 0.36 mV, and encapsulation efficiency more than 61%. The results of scanning electron microscopy revealed that nanoparticles have regular geometry with spherical shape. Initially the drug release occur through diffusion followed by erosion. The present studies showed that MTX-ES100 nanoparticles prepared during this study have the desired physicochemical properties, surface morphology and release characteristics used to target the desired organs.